The Supression of Migration and Metastasis via Inhibition of Vascular Endothelial Growth Factor in Pancreatic Adenocarcinoma Cells Applied Danusertib - Alabaş, Erkan; Özçimen, Ahmet Ata (Turkish Journal of Gastroenterology, 2024)
Background/Aims: Pancreatic ductal adenocarcinoma is an extremely deadly type of cancer with a high metastatic potential. Genetic factors in cellular events play an important role in the emergence of this situation. One of these factors is Aurora kinase family members, which play a role in migration, invasion, and cell cycle. In this study, the expression of vascular endothelial growth factor gene, which plays a role in migration, metastasis, and angiogenesis, on cystic fibrosis human pancreatic ductal adenocarcinoma 1 cells of danusertib, a pan-Aurora kinase inhibitor, was examined. Materials and Methods: The half maximal inhibitory concentration (IC50) value (400 nM) of danusertib in cystic fibrosis human pancreatic ductal adenocarcinoma 1 cells was determined by the wound-healing test depending on the dose and time and migration with CIM-Plate 16 in the xCELLingence system. In addition, the effect of danusertib on migration was determined by quantitative reverse transcription polymerase chain reaction (qRT-PCR) method and vascular endothelial growth factor gene expression. Results: When the dose- and time-dependent danusertib-applied cystic fibrosis human pancreatic ductal adenocarcinoma 1 cells were compared with the control group, it was observed that the wound formed did not close. In the xCELLigence system CIM-Plate 16 migration analysis, it was observed that migration was inhibited in the group administered danusertib in parallel with the wound dehiscence experiment. The gene expressions of vascular endothelial growth factor decreased 0.5-fold at the 24th hour and 0.3-fold at the 48th hour in the Danusertib-administered groups. Conclusion: Danusertib, a pan-Aurora kinase inhibitor, is predicted to be used as a potential agent in pancreatic cancers due to its antitumor and anti-metastatic effect. Cite this article as: Alabaş E, Özçimen AA. The supression of migration and metastasis via inhibition of vascular endothelial growth factor in pancreatic adenocarcinoma cells applied danusertib. Turk J Gastroenterol. 2024;35(2):150-157.